An Extensive Study of Issues, Challenges and Achievements in Iris Recognition - Swamilingappa Harakannanavar, Sunil; Prashanth, C. R.; Kanabur, Vidyashree; Puranikmath, Veena I.; K. B. Raja (Asian Journal of Electrical Sciences, 2019)
In recent years biometric identification of persons has gained major importance in the world from its applications, such as border security, access control and forensic. Iris recognition is one of the most booming biometric modalities. Due to its unique character as a biometric feature, iris identification and verification systems have become one of the most accurate biometric modality. In this paper, the different steps to recognize an iris image which includes acquisition, segmentation, normalization, feature extraction and matching are discussed. The performance of the iris recognition system depends on segmentation and normalization techniques adopted before extracting the iris features. It also provides an extensive review of the significant methods of iris recognition systems. In addition to this, the challenges and achievements of the iris are presented.